Pengaruh Gaya Hidup, Citra Merek, Media Sosial, dan Store Atmosfer Terhadap Keputusan Pembelian Konsumen pada Outlet Eiger Rajawali Palembang - Mario Tambos; Idham Cholid (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study was to determine the effect of Lifestyle, Brand Image, Social Media and Store Atmosphere on Purchasing Decisions at the Eiger Rajawali Palembang Outlet. The research sample was selected through a purposive sampling method with the slovin formula and produced 382 samples aimed at respondents who had purchased at the Eiger Rajawali Palembang Outlet. The research data were obtained from a questionnaire with a Likert scale, which was then analyzed by multiple regression analysis through the SPSS Statistics 23 apk. Based on the partial test (t-test), the research findings showed that Lifestyle and Brand Image had a significant effect on purchasing decisions, as seen from the sig value of 0.000 <0.05 and 0.000 <0.05. Social Media and Store Atmosphere did not have a significant effect on purchasing decisions, as seen from the sig value of 0.032> 0.05 and 0.0972> 0.05. The findings of the simultaneous test (F test) show that lifestyle, brand image, social media and store atmosphere have a significant effect on purchasing decisions, as seen from the sig value of 0.000 <0.05. The Determination Coefficient Test produces an Adjusted R Square of 0.245, meaning that the independent variable affects the dependent variable by 24.5%, and the remaining 75.5% from other factors.